HAYAL – QÍZLAR DÓRETIWSHILIGINIŃ JÁHÁN ÁDEBIYATTANÍW ILIMINDE IZERTLENIWI - Aliyeva, X.R. (SCIENCE and SOCIETY, 2021)
The article examines the level of creativity of women in fiction, their place in literature, the content and educational value of their works, as well as the study of female creativity in world literature